Treatment of cerebrospinal nematodiasis in a Boer Buck. Issue 1 (30th January 2019) - Breuer, Ryan; Merkatoris, Paul; Tepley, Samantha; Dierks, Caitlyn; Klostermann, Cassandra; Flaherty, Heather; Smith, Joseph
Abstract : A nine‐month‐old Boer Buck presented for an acute onset of pelvic limb ataxia. Radiographs, complete blood count and serum biochemistry were within normal limits. A cerebrospinal fluid analysis yielded an eosinophilic pleocytosis, consistent with cerebrospinal nematodiasis. Treatment with ivermectin, non‐steroidal anti‐inflammatories, fenbendazole and range of motion exercises resulted in partial recovery of pelvic limb function within five days. Within five months post treatment the buck's ambulation had returned to a normal gait.